Springtails (Collembola, Hexapoda) inhabiting algae with different degrees of waste product contamination - Izabella Olejniczak; Paweł Boniecki; Anita Kaliszewicz; Ninel Panteleeva (Studia Ecologiae et Bioethicae)
The study was carried out in July 2009 in Murmansk (68°57’ N; 33°03’E) and involved algae that had washed up at the edge of the intertidal zone of Kola Bay. Two areas of algae were selected for this study: uncontaminated (algae I) and algae contaminated with waste products (algae II). The material was collected using a frame with an area of 100 cm2. A total of 40 samples were taken. The abundance of the springtails was almost three times lower in the contaminated algae than in the uncontaminated algae, whereas the species diversity of the springtail communities was much higher in the contaminated algae. The littoral species Hypogastrura viatica was the dominant species in the uncontaminated algae, and that in the contaminated algae was the cosmopolitan species Folsomia quadriuculata. It appears that the contamination of the algae with waste products can promote the intensification of competition among springtails and between springtails and other saprophagous invertebrates.